1997
DOI: 10.1093/oxfordjournals.aje.a009195
|View full text |Cite
|
Sign up to set email alerts
|

Household and Dwelling Contact as Risk Factors for Leprosy in Northern Malawi

Abstract: Data on household and dwelling contact with known leprosy cases were available on more than 80,000 initially disease-free individuals followed up during the 1980s in a rural district of northern Malawi. A total of 331 new cases of leprosy were diagnosed among them. Individuals recorded as living in household or dwelling contact with multibacillary patients at the start of follow-up were at approximately five- to eightfold increased risk of leprosy, respectively, compared with individuals not living in such hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
91
3
27

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(131 citation statements)
references
References 8 publications
10
91
3
27
Order By: Relevance
“…There are many cases of leprosy of unknown origin in various countries, climates and topographies on the planet, even in regions that are considered free of the disease. Our study confirms this observation because 65% of all cases did not present any acknowledged contacts (de Wit et al 1993, Fine et al 1997, Richardus et al 2005, Deps et al 2008.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…There are many cases of leprosy of unknown origin in various countries, climates and topographies on the planet, even in regions that are considered free of the disease. Our study confirms this observation because 65% of all cases did not present any acknowledged contacts (de Wit et al 1993, Fine et al 1997, Richardus et al 2005, Deps et al 2008.…”
Section: Discussionsupporting
confidence: 87%
“…In Bangladesh, up to 75% of patients do not report contact with leprosy patients and, in Malawi, southern Africa, this was true for 85% of all cases. Perhaps the presence of bacillus in the environment or in asymptomatic carriers may help to explain such cases (de Wit et al 1993, Fine et al 1997, Matsuoka et al 1999, Richardus et al 2005, Lavania et al 2008.…”
Section: Discussionmentioning
confidence: 99%
“…A number of these antigens, including ML2028, ML2038 ) and the fusion protein LID-1 (Duthie et al 2010 have been shown to induce very strong antibody responses in virtually all BL/LL cases. A previous study in which HHCs of MB patients were bled four years prior to clinical diagnosis showed that seven/11 (64%) developed antibody re- A number of studies have shown that family members living in close contact with an untreated MB index case have the highest risk for developing this disease (Fine et al 1997, Cunanan et al 1998, van Beers et al 1999. In a large study involving 1,396 HHCs of index cases (79% of the index cases were MB) in Uberlândia, Brazil over a five-year period, 28 individuals were eventually diagnosed with leprosy, with 75% of those cases occurring within the first year of enrolment (Goulart et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Household contacts of multibacillary (MB) patients are at the highest risk to acquire the disease. 1 Host susceptibility to disease and to specific disease manifestations, notably severe (MB) or mild (paucibacillary (BP)) leprosy, is influenced by both host genetic and environmental factors. 2,3 Several genomic regions have been implicated in genetically controlled susceptibility to and severity of leprosy.…”
Section: Introductionmentioning
confidence: 99%